Weakening the weak may harm the strong: A bargaining model where opting-in is costly - Arno Riedl (Institute for Advanced Studies (IHS), 1995)
The opportunity to bargain often causes costs for at least one party in many economic situations, e.g. wage negotiations, joint ventures or interfirm cooperation. This paper studies such situations. A strong and a weak player have to agree how to divide the produced surplus. The weak player has to bear opting in costs. We characterize the set of subgame perfect equilibria. It is shown (i) that raising the costs of the weak party may strictly lower the payoff of the strong party, (ii) that for some cost levels the only equilibrium is inefficient, (iii) that if the players are sufficiently patient the outcomes of the zero-cost model and the vanishing costs version of our model do not coincide, and (iv) that in general multiplicity of equilibria arises. – – In vielen ökonomischen Situationen, wei z.B. Lohnverhandlungen, Joint Ventures oder anderen Formen der zwischenbetrieblichen Kooperation, hat zumindest eine der involvierten Parteien Verhandlungskosten zu tragen. Diese Arbeit analysiert solche Situationen. Ein starker und ein schwacher Spieler müssen ein Abkommen darüber treffen wei der von ihnen produzierte Surplus aufgeteilt werden soll. Der schwache Spieler ist derjenige welcher Eintrittskosten zu tragen hat. Die Menge der teilspielperfekten Gleichgewichte wird charakterisiert. Weiters wird gezeigt: (i) Eine Erhöhung der Eintrittskosten des schwachen Spielers bringt nicht immer einen Vorteil für den starken Spieler; (ii) für bestimmte Kostenniveaus ist das eindeutige Gleichgewicht ineffizient; (iii) Die Outcomes des Null-Kosten Modells und des präsentierten Modells mit verschwindenden Kosten stimmen nicht überein wenn die Spieler hinreichend geduldig sind; (iv) im allgemeinen existieren keine eindeutigen Gleichgewichte.
Keywords: C78; 330; noncooperative; bargaining